1983
DOI: 10.1007/bf00607084
|View full text |Cite
|
Sign up to set email alerts
|

Greatly enhanced bioavailability of theophylline on postprandial administration of a sustained release tablet

Abstract: The bioavailability of theophylline after oral administration of a new sustained release tablet Theograd-250 mg was studied in 7 healthy volunteers, under fasting and non-fasting conditions. Whilst fasting the bioavailability was moderate at 64 +/- 22% (mean +/- SD), whereas in the non-fasting state the relatively high bioavailability of 90 +/- 13% was found. The drug appeared to be significantly more slowly absorbed when a tablet was taken after a meal, than when it was ingested on an empty stomach. In the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Food decreases the rate of absorption (Leeds et al 1982;Osman et al 1983;Pedersen 1981;Thompson et al 1983) or its extent (Pedersen & Moller-Petersen 1984), increases both the rate and extent of absorption Hendeles et al 1984Hendeles et al , 1985Lagas & Jonkman 1983;Vaughan et al 1984), produces erratic changes (Pedersen & Moller-Petersen 1984) or Table II. Pharmacokinetic parameters of theophylline in 12 healthy male non-smokers after single 300mg doses of Theostat 300' taken while fasting and immediately after low-and high-fat content breakfasts Abbreviations: f = fasting; I = low-fat breakfast; h = high-fat breakfast: p < 0.05 compared with fasting.…”
Section: Discussionmentioning
confidence: 96%
“…Food decreases the rate of absorption (Leeds et al 1982;Osman et al 1983;Pedersen 1981;Thompson et al 1983) or its extent (Pedersen & Moller-Petersen 1984), increases both the rate and extent of absorption Hendeles et al 1984Hendeles et al , 1985Lagas & Jonkman 1983;Vaughan et al 1984), produces erratic changes (Pedersen & Moller-Petersen 1984) or Table II. Pharmacokinetic parameters of theophylline in 12 healthy male non-smokers after single 300mg doses of Theostat 300' taken while fasting and immediately after low-and high-fat content breakfasts Abbreviations: f = fasting; I = low-fat breakfast; h = high-fat breakfast: p < 0.05 compared with fasting.…”
Section: Discussionmentioning
confidence: 96%
“…Higher peak concentrations and bioavailability of theophylline after oral dosing have been observed when the drug is taken after a meal (Lagas & Jonkman, 1983) or with 500 ml of water (Welling et al, 1975). These studies were both performed using single doses of theophylline preparations.…”
Section: Dscussionmentioning
confidence: 99%
“…As the elimination half-life of theophylline is short (4-9 h), 4-to 6-hourly administration of IR dosage forms is required to maintain the serum concentration within the therapeutic range (12). With such a regimen, lack of patient compliance is a serious problem, and low trough levels in the morning, with a possible risk of breakthrough of symptoms, can occur (13). Accordingly, ER dosage forms are the formulations most favored for the long-term management of chronic bronchospasm.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that in many cases, drug release from various theophylline ER formulations could be influenced (either increased or decreased) by concomitant intake of food (1,3,(14)(15)(16)(17)(18). Although in maintenance therapy of chronic obstructive lung disease, most drugs are given in conjunction with food, the recent literature contains very few in vivo studies (1,5,13,(18)(19)(20) and next to no in vitro investigations (21) of the influence of food on the bioavailability of theophylline from ER formulations. Food intake can influence the rate of drug release from the dosage form, the rate of drug absorption, the amount of drug absorbed, or all of these parameters simultaneously.…”
Section: Introductionmentioning
confidence: 99%